The insertion of the activities of the nutritionist within the scope of the PNAE in schoolchildren in the municipality of Picuí-PB (Research, Society and Development, 2021)
Being one of the oldest public food complementation programs, the National School Feeding Program (PNAE) enjoys proposals such as supplementation of the daily needs of enrolled students, with the objective of ensuring Food and Nutrition Security (SAN) and collaborating for the formation of good eating habits. Obesity and/or overweight are associated with the quantity and quality of children's food intake, a phase where it is not totally independent and has no autonomy in its choices, including their preferences. The study aims to perform and analyze anthropometry to identify health problems related to children's diet. The same research also aimed to identify the percentages of acceptance of the menus, in order to recognize probable sensory inadequacies in the meals offered. The results obtained portrayed characteristics of the nutritional transition, which is marked by the increase in the overweight/obesity indicator, making it necessary to pay close to the fact that, even if the percentages of eutrophy have increased in comparison to the other classifications, the presence of children under or above the recommended weight and/or height should not be ruled out. The sensory evaluation showed that the preparation was not well accepted obtaining the average level of adesand similarly in the daycare center, it was not a good acceptability due to the well-marked characteristics of the dish served, one of which is the taste of the main ingredient of the meal. It is concluded that the students need actions aimed at nutritional education and the menu served should be rethought.